2007
DOI: 10.1200/jco.2006.06.3743
|View full text |Cite|
|
Sign up to set email alerts
|

An Integrated Genomic-Based Approach to Individualized Treatment of Patients With Advanced-Stage Ovarian Cancer

Abstract: We have defined a strategy for treatment of patients with advanced-stage ovarian cancer that uses therapeutic stratification based on predictions of response to chemotherapy, coupled with prediction of oncogenic pathway deregulation, as a method to direct the use of targeted agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
231
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(238 citation statements)
references
References 32 publications
6
231
0
1
Order By: Relevance
“…It is tempting to speculate that under certain circumstances, E2F activity might aid in the development of drug resistance through stimulating FA pathway activity and DNA repair. Interestingly, gene expression signatures of platinum-resistant advanced stage ovarian cancers revealed activation of E2F3 pathways, and the targeting of E2F pathways with roscovitine could be exploited for improved response to chemotherapy in vitro (Dressman et al, 2007). Additionally, high levels of activating relative to repressing E2Fs have recently been shown to be clinical predictors of poor response to chemotherapy in ovarian cancer patients (Reimer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that under certain circumstances, E2F activity might aid in the development of drug resistance through stimulating FA pathway activity and DNA repair. Interestingly, gene expression signatures of platinum-resistant advanced stage ovarian cancers revealed activation of E2F3 pathways, and the targeting of E2F pathways with roscovitine could be exploited for improved response to chemotherapy in vitro (Dressman et al, 2007). Additionally, high levels of activating relative to repressing E2Fs have recently been shown to be clinical predictors of poor response to chemotherapy in ovarian cancer patients (Reimer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, aberrant expression and activation of the SFKs have been described in human ovarian cancer cell lines (Budde et al, 1994) and clinical samples (Wiener et al, 2003). A recent study used gene expression signatures that define the status of Src signalling pathways to predict the probability of Src pathway activation in 119 patients with ovarian cancer (Dressman et al, 2007). Approximately half of the tumours examined in this study showed Src pathway deregulation.…”
mentioning
confidence: 99%
“…It might then be possible to study physiological processes in one type of cancer and extrapolate the results predictively to another type through commonalities in their molecular constitutions. More recently, several studies have demonstrated that genomic biomarkers can be used to predict chemotherapeutic responses of human cancer patients (6)(7)(8).…”
mentioning
confidence: 99%